Behavioral Evidence of HIV Testing Stigma - Young, Sean (2012)
To avoid HIV testing stigma, people may engage in non-stigmatized behaviors to conceal their interest in HIV testing. We examined 165,828 outpatient visits in a 2002-2007 national survey to explore whether people receiving an HIV diagnostic test, compared to people receiving non-stigmatized, diagnostics tests (mammography and blood pressure testing), listed their interest in testing more frequently as a non-primary reason for visit, listed a greater number of reasons for visiting the clinic, and listed more reasons for visit unrelated to the testing performed. Among people who reported HIV testing as a reason for visit, 42.39% requested HIV testing as a non-primary reason for visit (mammography: 13.77%; blood pressure: 18.01%), and on average listed more reasons for visiting the clinic. The odds of requesting additional unrelated services for HIV testing patients was almost 5 times that of patients requesting blood pressure tests and over 20 times the odds of mammography patients. Together, we interpret these results as initial behavioral evidence of people's avoidance of HIV stigma in health care settings. We hope that this manuscript serves as a call to action for future research exploring causal relationships between health service usage and HIV stigma.